A Foresight Study on the Adoption of Building Automation System in Malaysia - Salim, Siti Aisyah; Sumari, Alina (Research in Management of Technology and Business, 2022)
: Building automation system (BAS) is a system that manages the electrical and mechanical systems in a building. The usage of electrical energy in most countries goes up to 40 percent which is equivalent to 39 percent of process related carbon dioxide emissions. Malaysia is one of the countries that have high consumption of electricity contributed from different sectors. The discussion on the adoption and practicality of BAS technology is still lacking in the context of Malaysia. Thus, the aim of this study is to identify the key drivers of the BAS adoption and to determine the future trends of BAS adoption in Malaysia. In this study, a mixed method approach was used which included STEEPV and a quantitative study. The quantitative study is conducted by distributing the questionnaires to the green building developers in Malaysia. Impact uncertainty is analysed based on the key drivers and issues from the qualitative and quantitative methods. Ten merged key drivers and issues had been identified from the STEEPV method. The impact-uncertainty analysis approach had been used to identify the future trends of BAS adoption. About 50 questionnaires had been distributed with response rate 64.00%. This study found that resources of work efficiency and effectiveness to reduce energy consumptions had the highest impact and uncertainty. Four scenarios were proposed at the end of the study. The four scenarios were sustainable development of BAS, stagnant or sluggish technology, achieved green certification and improved comfort and experience.